Wage and Employment Effects of Payroll Taxes and Investment Subsidies - Frode Johansen; Tor Jakob Klette (Statistics Norway, Research Department, 1997)
Using a panel of manufacturing plants we study how payroll taxes and investment subsidies affect wages and demand for labor and capital. We exploit the regional subsidy schemes for labor and capital in Norway. Our empirical analysis finds that a large part of changes in payroll taxes is shifted over to wages. This result suggests that changes in payroll taxes have a limited direct effect on employment. Our study of investment subsidies finds evidence of substitution between labor and capital, with an elasticity of substitution of about 0.4 at the plant level. This indicates that increased taxation of capital will have a positive substitution effect on the demand for labor
Keywords: E24; H25; 330; Wages; Labor Demand; Business Taxation